Center Region Relations and National Cohesion in Indonesia - Slamet Riyanto; Ahmad Ahmad (Indonesian Journal of Law and Policy Studies, 2025)
This article examines the long-term challenge of national integration in Indonesia through the historical development of constitutional arrangements and their interaction with contemporary governance practices. It explains how federalism, unitarism, and center–region relations continue to influence political stability and national cohesion. The study applies normative legal research supported by historical and conceptual analysis. Primary materials include constitutional documents and state policies, while secondary materials cover scholarly works on decentralization, separatism, governance, and disaster management. The findings show that Indonesia’s integration problems are rooted in structural inequality, unresolved historical legacies, and governance practices that reinforce perceptions of regional marginalization. The article also finds that federalism operates less as a realistic constitutional alternative than as a symbolic political discourse that re-emerges during crises, including the 2025 hydrometeorological disaster in Sumatra. It concludes that constitutional design alone is insufficient to sustain national integration without inclusive governance, equitable development, institutional responsiveness, and stronger public trust